PENERAPAN KETENTUAN AMBANG BATAS BAKU MUTU LINGKUNGAN UDARA DALAM PEMBUKTIAN TINDAK PIDANA LINGKUNGAN AKIBAT KEBAKARAN HUTAN BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Sally Fisabillina; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
To determine the damage criteria and criteria for exceeding environmentalquality standards, an expert who indeed controls the field of environmental damage isrequired. Not only experts but conclusions for damage and exceeding quality standardsmust also be proven by accredited laboratory tests. The research entitled "Application ofAir Environmental Quality Standard Threshold Provisions in Proving EnvironmentalCrimes Due to Forest Fires Based on Law Number 32 of 2009 concerning EnvironmentalProtection and Management", has a formulation of the problem of how to apply theprovisions for the threshold of air quality standards in proof criminal offenses due toforest fires, and what is the strength of evidence by expert witnesses in environmentalcrimes due to forest fires from laboratories that are not accredited.The purpose of this thesis is: first, to find out the application of the provisions ofthe threshold of air quality quality standards in proving forest crime. Second, todetermine the strength of proof of environmental crime due to forest fires fromlaboratories that are not accredited.This type of research is normative legal research or can be referred to asdoctrinal legal research. From the results of the problem research there are two mainthings which are concluded, first, in the case of proof of environmental crime due toforest fires, it is closely related to scientific procedures according to legal conditions. Themeans that can be used to determine the excess of quality standards are laboratories.One important aspect that can affect the effectiveness and efficiency of whether or notenvironmental management in a country or region is whether or not a laboratory isavailable, in this case an environmental laboratory that is capable of delivering valid andrelible, irrefutable, scientifically and legally accountable data. Secondly, evidence ofexpert testimony does not have a binding and decisive value of proof power. The value ofthe power of proof of expert testimony is the same as the value of the evidentiary powerinherent in the evidence evidence of the witness or the defendant. Therefore, the value ofthe evidentiary power attached to the evidence of expert testimony must be supported byother evidence.